Bridges of biomaterials promote nigrostriatal pathway regeneration. Issue 1 (23rd March 2018) - Gómez‐Pinedo, Ulises; Sanchez‐Rojas, Leyre; Vidueira, Sandra; Sancho, Francisco J.; Martínez‐Ramos, Cristina; Lebourg, Myriam; Monleón Pradas, Manuel; Barcia, Juan A.
Abstract: Repair of central nervous system (CNS) lesions is difficulted by the lack of ability of central axons to regrow, and the blocking by the brain astrocytes to axonal entry. We hypothesized that by using bridges made of porous biomaterial and permissive olfactory ensheathing glia (OEG), we could provide a scaffold to permit restoration of white matter tracts. We implanted porous polycaprolactone (PCL) bridges between the substantia nigra and the striatum in rats, both with and without OEG. We compared the number of tyrosine‐hydroxylase positive (TH+) fibers crossing the striatal‐graft interface, and the astrocytic and microglial reaction around the grafts, between animals grafted with and without OEG. Although TH+ fibers were found inside the grafts made of PCL alone, there was a greater fiber density inside the graft and at the striatal‐graft interface when OEG was cografted. Also, there was less astrocytic and microglial reaction in those animals. These results show that these PCL grafts are able to promote axonal growth along the nigrostriatal pathway, and that cografting of OEG markedly enhances axonal entry inside the grafts, growth within them, and re‐entry of axons into the CNS. These results may have implications in the treatment of diseases such as Parkinson's and others associated with lesions of central white matter tracts. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 190–196, 2019.